9(x+4)+x=3(x+5)-8

Simple and best practice solution for 9(x+4)+x=3(x+5)-8 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9(x+4)+x=3(x+5)-8 equation:


Simplifying
9(x + 4) + x = 3(x + 5) + -8

Reorder the terms:
9(4 + x) + x = 3(x + 5) + -8
(4 * 9 + x * 9) + x = 3(x + 5) + -8
(36 + 9x) + x = 3(x + 5) + -8

Combine like terms: 9x + x = 10x
36 + 10x = 3(x + 5) + -8

Reorder the terms:
36 + 10x = 3(5 + x) + -8
36 + 10x = (5 * 3 + x * 3) + -8
36 + 10x = (15 + 3x) + -8

Reorder the terms:
36 + 10x = 15 + -8 + 3x

Combine like terms: 15 + -8 = 7
36 + 10x = 7 + 3x

Solving
36 + 10x = 7 + 3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-3x' to each side of the equation.
36 + 10x + -3x = 7 + 3x + -3x

Combine like terms: 10x + -3x = 7x
36 + 7x = 7 + 3x + -3x

Combine like terms: 3x + -3x = 0
36 + 7x = 7 + 0
36 + 7x = 7

Add '-36' to each side of the equation.
36 + -36 + 7x = 7 + -36

Combine like terms: 36 + -36 = 0
0 + 7x = 7 + -36
7x = 7 + -36

Combine like terms: 7 + -36 = -29
7x = -29

Divide each side by '7'.
x = -4.142857143

Simplifying
x = -4.142857143

See similar equations:

| -5(y-3y)+9=3(2y-y)+1+12y | | .50c+.40-400=190 | | 0.05x-2.75=0.3(x-5) | | 3=-3(x+4) | | -1x+9=7x+5 | | 6x+2-15=-15 | | .50c+.40=400 | | -3(x+4)+4=7(x+4)+3 | | 5(x-7)+10=3(x-5) | | h(t)=2t-t^2 | | 5sinx+7cosx=8 | | 12x-8=9x-8 | | x-4=-24-9x | | .50c+400=.40 | | (2x-5)=15 | | -3(t-5)+7t=6t-5 | | 2=x/6.4 | | 6-14=6+(-8) | | (a^4+4a+-8)=0 | | 12x^2y+18xy-6x=0 | | f(x)=15x^4-15x^2 | | a^4+4a-8=0 | | 45=7-2b | | 1/4x0.04 | | 12/7=k//8 | | .50c+.40=190 | | -4=6+2x | | 1.7=k/8 | | Log(x)=-8 | | r-9.8=-2.4 | | 4s=s-3 | | 5y+ax=0 |

Equations solver categories